The Role of Enterococcus faecium as a Key Producer and Fermentation Condition as an Influencing Factor in Tyramine Accumulation in Cheonggukjang - Young Kyoung Park (Foods, 2020)
The study evaluated the role of Enterococcus faecium in tyramine production and its response to fermentation temperature in a traditional Korean fermented soybean paste, Cheonggukjang. Tyramine content was detected in retail Cheonggukjang products at high concentrations exceeding the recommended limit up to a factor of 14. All retail Cheonggukjang products contained Enterococcus spp. at concentrations of at least 6 Log CFU/g. Upon isolation of Enterococcus strains, approximately 93% (157 strains) produced tyramine at over 100 µg/mL. The strains that produced the highest concentrations of tyramine (301.14–315.29 μg/mL) were identified as E. faecium through 16S rRNA sequencing. The results indicate that E. faecium is one of the major contributing factors to high tyramine content in Cheonggukjang. During fermentation, tyramine content in Cheonggukjang groups co-inoculated with E. faecium strains was highest at 45 °C, followed by 37 °C and 25 °C. The tyramine content of most Cheonggukjang groups continually increased as fermentation progressed, except groups fermented at 25 °C. At 45 °C, the tyramine content occasionally exceeded the recommended limit within 3 days of fermentation. The results suggest that lowering fermentation temperature and shortening duration may reduce the tyramine content of Cheonggukjang, thereby reducing the safety risks that may arise when consuming food with high tyramine concentrations.